Degenerative changes in the appendicular joints of ancient human populations from the Japan Islands. (16th June 2016) - Suzuki, Shinji; Sunagawa, Masanobu; Shindo, Misaki; Kimura, Ryosuke; Yamaguchi, Kyoko; Sato, Takehiro; Yoneda, Minoru; Nagaoka, Tomohito; Saiki, Kazunobu; Wakebe, Tetsuaki; Hirata, Kazuaki; Tsurumoto, Toshiyuki; et al.
Abstract: Degenerative changes in six major limb joints were investigated to compare their prevalence among five ancient skeletal populations from the Japan Islands. The populations assessed in this study consisted of the farmers in the northern Kyushu/Yamaguchi area and the foragers from the northwestern Kyushu area from the Yayoi period (5th century BC to 3rd century AD); the Okhotsk (5th to 12th centuries AD) foragers from Hokkaido and Sakhalin; the common people from medieval Kamakura (12th to 14th centuries AD) in Kanto, central Japan; and the early-modern farmers (17th to 19th centuries AD) from Kumejima, in the southernmost island chain (Ryukyu Islands). Crude prevalence comparisons showed that the shoulder and hip joints were principally affected in early-modern Kumejima and medieval Kamakura, which contrasted with the high prevalence of elbow and knee joint changes in the Okhotsk people. The heavy dependence on marine mammals and fish for dietary protein intake probably required flexion and extension movements of the most severely degenerated joints in the Okhotsk people. The northern Kyushu/Yamaguchi and northwestern Kyushu Yayoi peoples were more affected by degeneration in the wrist joints than others, possibly due to their use of innovative tools such as stone or shell knives and harpoons. A multivariate logistic regression analysis, adjusted for age, region, and sex as the predictor variables for degenerative changes in joints, was applied to only the two samples from Kumejima and Kamakura (including previously reported spine data) because of their better preservation. This revealed differences in the prevalence of changes in some joints; for example, age-related changes were recognized. The Kumejima people were more commonly affected by hip and knee joint changes, whereas the Kamakura people were more commonly affected by changes to apophyseal joints. Because a stable isotope analysis indicated that the trophic levels of the two populations were almost the same, the pattern of degenerative changes would have reflected differences in their specific workloads, such as wet rice cultivation using a peculiar hoe by the Kumejima people. This study, combining multivariate logistic regression analysis of degenerative joint changes and stable isotope analyses, uses large skeletal populations to add clarity to the actual rigors of ancient life.